What Predicts and what Mediates the response of urge urinary incontinence to biofeedback?123. Issue 5 (20th November 2012) - Resnick, Neil M.; Perera, Subashan; Tadic, Stasa; Organist, Linda; Riley, Mary Alyce; Schaefer, Werner; Griffiths, Derek
Abstract Aims To better target a behavioral approach for urge urinary incontinence (UUI) and enhance its efficacy by (1) identifying predictors of response to biofeedback‐assisted pelvic muscle training (BFB), and (2) determining factors that mediate response. Methods BFB (four biweekly visits) was administered to 183 women > 60 years (mean = 73.6). Before and after intervention, all underwent comprehensive evaluation and videourodynamic testing. Postulated predictors and mediators from four urodynamic domains, specified a priori, were correlated with reduction in UUI frequency. Results Median UUI frequency decreased from 3.2/day to 1/day (P =0.0001). UUI improved by ≥50% in 55% of subjects and by 100% in 13% of subjects. Frequent UUI predicted poor response (P < 0.01). Of the urodynamic parameters, only high amplitude and briskness of detrusor overactivity (DO) predicted decreased response (P < 0.05 and P < 0.01) and these could be measured only in the 43% of subjects with elicitable DO. Decreased DO elicitability was the only urodynamic variable that changed in concert with improvement and thus was a candidate mediator. Response was neither predicted nor mediated by proprioception/warning, cystometric capacity, detrusor contractility, sphincter strength, or baseline DO elicitability. Conclusions Severe DO predicts poor response to BFB. Good response is mediated by reduction in DO elicitability. Other than baseline UUI frequency, there are no other clinically or urodynamically important predictors or mediators of BFB response in this population. BFB may be best for patients with less severe DO. Future research to enhance its efficacy might better focus on the brain than on the lower urinary tract. Neurourol. Urodynam. 32: 408–415, 2013. © 2012 Wiley Periodicals, Inc.